The Influence of Pronunciation on Students’ Speaking Confidence - Arsi, Aliah Khusna; Farahdiba, Syarifah; Ariyani, Amra (Program Studi Pendidikan Bahasa Inggris FBS UNM, 2025)
This research aimed to find out whether or not pronunciation influences students’ speaking confidence. The research focused on 125 tenth-grade students from MAN 2 Soppeng as the population. The research instrument was questionnaires (pre-questionnaire and post-questionnaire) to assess changes in speaking confidence before and after treatment. The study employed a pre-experimental design with a one-group pretest-posttest approach, selecting a sample of 19 students from class X3 using cluster random sampling. Data analysis was conducted using IBM SPSS 23 Version. The findings indicated that pronunciation does influence students’ speaking confidence, as evidenced by an Asymp. Sig. (2-tailed) value of 0.001 from the Wilcoxon nonparametric test. Since the result is less than 0.05, it can be said that the hypothesis was accepted. Thus, it can be concluded that pronunciation influences students' speaking confidence in class X3 at MAN 2 Soppeng.